ILSI Europe perspective review: site-specific microbiota changes during pregnancy associated with biological consequences and clinical outcomes: opportunities for probiotic interventions - Eduard Flores Ventura; Jonathan A. Lane; Sondra Turjeman; Nikoletta Vidra; Gisela Adrienne Weiss; Gabriele Gross; Ching-Yu Chang; Omry Koren (Gut Microbes)
Pregnancy induces notable alterations in the gut, vaginal, and oral microbiota driven by hormonal, immune, metabolic, dietary, and environmental factors. During pregnancy, the gut microbiota is characterized by increased proportions of the genus Bifidobacterium and the phyla Pseudomonadota (formerly Proteobacteria) and Actinomycetota (formerly Actinobacteria). These changes occur alongside reduced alpha diversity and greater beta diversity, changes that influence maternal metabolism and fetal development. Shifts in gut and oral microbiota have been associated with complications such as preterm birth (PTB), pre-eclampsia, and gestational diabetes (GDM), though patterns are sometimes inconsistent. The vaginal microbiota remains Lactobacillus-dominant during pregnancy, with reduced diversity leading to reduced risk of pathogenic infection and increased diversity has been linked with a higher risk of PTB. Hormonal changes also affect the oral microbiota, potentially increasing pathogenic species and contributing to adverse outcomes like PTB. Probiotic supplementation during pregnancy has significant potential to reduce adverse pregnancy outcomes; however, clinical studies are still limited. Probiotics may be effective in alleviating maternal constipation and lead to lower PTB risk, particularly by modulating the vaginal microbiota, but they have limited impact on GDM. In the context of maternal mental health, some studies suggest benefits of probiotics in reducing anxiety, but effects on depression are inconclusive. This perspective examines how pregnancy-related microbial shifts, both natural and probiotic-induced, affect maternal and fetal health and highlights potential opportunities for the innovative use of probiotics during the gestation period.